Overview of security problems and the design of secure electronic system - Gorbachov, V.A.; Abdulrahman, K.B. (Radiotekhnika, 2017)
The classification and methods of fighting Hardware Trojans are analyzed. The choice of the technology for the design of protected electronic systems is justified, which ensures their resistance to the destructive effect of internal components.